A goal-based angular adaptivity method for thermal radiation modelling in non grey media. (October 2017) - Soucasse, Laurent; Dargaville, Steven; Buchan, Andrew G; Pain, Christopher C
Highlights: A goal-based angular adaptivity method is derived for radiative transfer in non grey media. Angular resolution is optimised to accurately compute the radiative source term. Haar wavelet angular expansion is used to perform anisotropic adaptivity. The method is assessed in a coupled flow-radiation problem relevant for air pollution modelling in street canyons. Abstract: This paper investigates for the first time a goal-based angular adaptivity method for thermal radiation transport, suitable for non grey media when the radiation field is coupled with an unsteady flow field through an energy balance. Anisotropic angular adaptivity is achieved by using a Haar wavelet finite element expansion that forms a hierarchical angular basis with compact support and does not require any angular interpolation in space. The novelty of this work lies in (1) the definition of a target functional to compute the goal-based error measure equal to the radiative source term of the energy balance, which is the quantity of interest in the context of coupled flow-radiation calculations; (2) the use of different optimal angular resolutions for each absorption coefficient class, built from a global model of the radiative properties of the medium. The accuracy and efficiency of the goal-based angular adaptivity method is assessed in a coupled flow-radiation problem relevant for air pollution modelling in street canyons. Compared to a uniform Haar wavelet expansion, the adapted resolution uses 5 times fewer angular basis functions and is 6.5 times quicker, given the same accuracy in the radiative source term.